SOCIAL VALUES ​​IN THE FOLK LITERATURE OF PANDIT JAGANNATH - Navita; Sharmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social values ​​are those principles which govern the behaviour and actions of people in any society. These values ​​are based on social behaviour, sensitivity and mutual respect and create a well-organised society. The major social values ​​include respect for others, respect for mutual views, cooperation, truthfulness, honesty, justice to all, equal behaviour, compassion towards others, sense of performing one's duties and maintaining goodwill in the society. These values ​​spread unity, happiness and peace in the society and make people responsible and sensitive towards each other. The present research paper describes the social values ​​contained in the folk literature of Pandit Jagannath. Pandit Jagannath was a famous folk poet and singer of Haryana. Social values ​​have a special place in Pandit Jagannath's folk literature which emphasizes the principles of morality, duty, preservation of cultural heritage and equality in the society. The purpose of his folk literature is to propagate the spirit of morality and unity in the society. Values ​​touching various aspects of society have been presented very deeply in Pandit Jagannath's literature. His writings promote the spirit of collectivism, cooperation and brotherhood which is the basis of the strength of any society. His literature teaches harmony and co-existence among different religions, castes and communities in the society. He believes that society can develop only when all people live together in unity and love. Morality and sense of duty have a paramount place in Pandit Jagannath's folk literature. Social values ​​like ideal behavior, truthfulness, honesty and duty fulfillment have been discussed in his works which make a person aware of right and wrong and develop the qualities of a good citizen in the society.